2011
DOI: 10.1111/j.1475-6811.2011.01363.x
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents and consequences of interpersonal forgiveness: A meta‐analytic review

Abstract: This article examines the antecedents and outcomes of forgiveness. The interpersonal forgiveness literature is qualitatively reviewed. Antecedents to forgiveness are classified by their proximity to forgiveness based on M. E. McCullough and colleagues, (1998) framework. From most distal to most proximal these antecedents are personality, relationship factors, offense-specific factors, and social-cognitive factors including empathy. The association of these antecedents and several consequences of forgiveness ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
4
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(160 citation statements)
references
References 101 publications
(152 reference statements)
3
147
4
6
Order By: Relevance
“…Thompson et al, 2005;Eaton, Struthers, & Santelli, 2006;Drinnon & Jones, 2009) and related to different variables (e.g. Allemand et al, 2007;Fehr, Gelfand, & Nag, 2010;Riek & Mania, 2012). That is because forgiveness in a particular situation involves factors that are both intrinsic (among others dispositional forgiveness) and extrinsic (specific contextual aspects) to individuals (Koutsos, Wertheim, & Kornblum, 2008), while disposition to forgive, apart from multiple circumstances, depends primarily on personality characteristics (Paleari, Regalia, & Fincham, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thompson et al, 2005;Eaton, Struthers, & Santelli, 2006;Drinnon & Jones, 2009) and related to different variables (e.g. Allemand et al, 2007;Fehr, Gelfand, & Nag, 2010;Riek & Mania, 2012). That is because forgiveness in a particular situation involves factors that are both intrinsic (among others dispositional forgiveness) and extrinsic (specific contextual aspects) to individuals (Koutsos, Wertheim, & Kornblum, 2008), while disposition to forgive, apart from multiple circumstances, depends primarily on personality characteristics (Paleari, Regalia, & Fincham, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, respondents fail to consider various relationship factors when imagining transgressions (McCullough & Hoyt, 2002). Also, the effect of religiosity, attributions, and negative emotions are shown to be stronger in hypothetical forgiveness compared to actual forgiveness (Riek & Mania, 2012).…”
Section: Limitations Implications and Future Researchmentioning
confidence: 99%
“…Meta-analytic evidence suggests that deficits in agreeableness may be the most robust predictor of revenge intentions and interpersonal conflict across a variety of situations (Bettencourt, et al, Lourdes rey, NataLio extremera ;riek & Mania, 2012). Nevertheless, studies into potential gender differences in the association between this dispositional quality and forgiveness have been scarce.…”
Section: Discussionmentioning
confidence: 99%
“…earlier research has found that a disposition to forgive is related most strongly to two specific higher-order dimensions of the five-factor personality domains: agreeableness and neuroticism (Mccullough, 2001;Mullet, Neto & rivière, 2005). cumulative meta-analytic evidence suggests that agreeableness may be the most robust predictor of forgiveness (Riek & Mania, 2012) and interpersonal conflict (Bettencourt, Talley, Benjamin & Valentine 2006;Jensen-Campbell & graziano, 2001), existing less empirical consensus with neuroticism. people who are low in agreeableness are antagonistic, hostile, irritable, and mistrustful of others; they also seem to have a need to punish people that they perceive to have provoked them, which might contribute to a lower dispositional tendency to forgive others (lee & Ashton, 2012) and higher levels of interpersonal conflict (Jensen-Campbell, Gleason, Adams & Malcolm, 2003).…”
Section: Introductionmentioning
confidence: 99%